Large‐effect loci affect survival in Tasmanian devils (Sarcophilus harrisii) infected with a transmissible cancer. Issue 21 (5th October 2018) - Margres, Mark J.; Jones, Menna E.; Epstein, Brendan; Kerlin, Douglas H.; Comte, Sebastien; Fox, Samantha; Fraik, Alexandra K.; Hendricks, Sarah A.; Huxtable, Stewart; Lachish, Shelly; Lazenby, Billie; O'Rourke, Sean M.; et al.
Abstract: Identifying the genetic architecture of complex phenotypes is a central goal of modern biology, particularly for disease‐related traits. Genome‐wide association methods are a classical approach for identifying the genomic basis of variation in disease phenotypes, but such analyses are particularly challenging in natural populations due to sample size difficulties. Extensive mark–recapture data, strong linkage disequilibrium and a lethal transmissible cancer make the Tasmanian devil ( Sarcophilus harrisii ) an ideal model for such an association study. We used a RAD‐capture approach to genotype 624 devils at 16, 000 loci and then used association analyses to assess the heritability of three cancer‐related phenotypes: infection case–control (where cases were infected devils and controls were devils that were never infected), age of first infection and survival following infection. The SNP array explained much of the phenotypic variance for female survival (>80%) and female case–control (>61%). We found that a few large‐effect SNPs explained much of the variance for female survival ( 5 SNPs explained >61% of the total variance), whereas more SNPs ( 56) of smaller effect explained less of the variance for female case–control ( 23% of the total variance). By contrast, these same SNPs did not account for a significant proportion of phenotypic variance in males, suggesting that the genetic bases of these traits and/or selection differ across sexes. Loci involved with cell adhesion and cell‐cycle regulation underlay trait variation, suggesting that the devil immune system is rapidly evolving to recognize and potentially suppress cancer growth through these pathways. Overall, our study provided necessary data for genomics‐based conservation and management in Tasmanian devils.